Annealing disorder and photoinduced order of oxygen chains in detwinned YBa2Cu3O6.65 single crystals probed by Raman scattering - Fainstein, A.; Maiorov, B.; Guimpel, J.; Nieva, G.; Osquiguil, E.; Guimpel, Julio; Nieva, Gladys (American Physical Society, 2000)
Fil: Fainstein, A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina